Penegakan Hukum terhadap Kekerasan Seksual dalam Lingkungan Perguruan Tinggi di Indonesia - Pusdikawati, Rani; Jamaludin, Ahmad (UNES Law Review, 2023)
Sexual violence has become an urgent issue in Indonesian higher education institutions. The increased freedom and diversity in campus social interactions make students vulnerable to becoming victims. The rising number of reports and cases of sexual violence in universities has serious consequences for the victims and disrupts the academic climate and quality of education. Addressing sexual violence in higher education institutions poses unique challenges due to factors such as the lack of awareness about victims' rights, feelings of shame or fear in reporting incidents, and the potential intimidation from related parties, which often hinder law enforcement efforts. Therefore, enforcing laws against sexual violence in university settings becomes crucial. This research employs a normative juridical method with a qualitative approach. Data is collected through library studies and research on relevant literature and documents. The research aims to describe the symptoms of sexual violence in higher education institutions and identify law enforcement and prevention efforts that have been implemented.As a step to address sexual violence in higher education institutions, on May 9, 2022, the President of the Republic of Indonesia approved Law No. 12 of 2022 on Sexual Violence Criminal Acts. Additionally, the government has issued Minister of Education, Culture, Research, and Technology Regulation No. 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Institutions.Preventive and handling efforts for sexual violence are conducted by establishing task forces in universities, formulating prevention and handling guidelines, providing training and socialization on gender equality and sexual health education, as well as offering reporting services for sexual violence. With effective implementation of these laws and policies, it is hoped that sexual violence in higher education institutions can be minimized, ensuring a conducive learning environment and providing positive impacts for the entire academic community.